2022
DOI: 10.3389/fmicb.2022.846890
|View full text |Cite
|
Sign up to set email alerts
|

Community Interaction Co-limitation: Nutrient Limitation in a Marine Microbial Community Context

Abstract: The simultaneous limitation of productivity by two or more nutrients, commonly referred to as nutrient co-limitation, affects microbial communities throughout the marine environment and is of profound importance because of its impacts on various biogeochemical cycles. Multiple types of co-limitation have been described, enabling distinctions based on the hypothesized mechanisms of co-limitation at a biochemical level. These definitions usually pertain to individuals and do not explicitly, or even implicitly, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 120 publications
0
12
0
Order By: Relevance
“…For example, experiments show that iron can be limiting for bacterial growth in the surface ocean (Church et al., 2000) and potentially in the mesopelagic (Baltar et al., 2018), although a global modeling study found it to be not the main limiting factor (Pham et al., 2022). Similarly, community‐aspects of co‐limitations have not been included here (Bannon et al., 2022). Global models intentionally generalize and simplify, and assessing such microbial community effects on global scales using Earth System Models is currently out of reach, because the huge diversity of compounds and microorganisms still poses a huge challenge to models, and heterotrophic microorganisms are usually not even included.…”
Section: Resultsmentioning
confidence: 99%
“…For example, experiments show that iron can be limiting for bacterial growth in the surface ocean (Church et al., 2000) and potentially in the mesopelagic (Baltar et al., 2018), although a global modeling study found it to be not the main limiting factor (Pham et al., 2022). Similarly, community‐aspects of co‐limitations have not been included here (Bannon et al., 2022). Global models intentionally generalize and simplify, and assessing such microbial community effects on global scales using Earth System Models is currently out of reach, because the huge diversity of compounds and microorganisms still poses a huge challenge to models, and heterotrophic microorganisms are usually not even included.…”
Section: Resultsmentioning
confidence: 99%
“…In nature, colimitation of clonal populations is also layered with community colimitation, for instance, when members of the community have different nutrient preferences [31, 32]. In this case, the starting conditions of the system are even less clear than for clonal populations, and supplementation experiments that scan a surface of nutrient concentrations in multiple dimensions provide a critical advantage for quantifying the extent of limitation and the number of limiting resources.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates suggest that co‐limitation of marine microbial populations is a common phenomenon (Browning et al., 2017), and may affect the food‐web dynamics, the organism's nutritional requirements, and species distribution (Bannon et al., 2022). Currently, it is very hard to study this issue experimentally, especially because we lack a detailed understanding of individual phytoplankton/bacteria's nutritional requirements, community dynamics etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from the SEMS coast showed that phytoplankton are primarily N‐limited, while heterotrophic prokaryotes are limited by organic carbon substrates and/or orthophosphate (Rahav et al., 2016). Given that many marine microorganisms are vitamin B 12 auxotrophs (Bannon et al., 2022), and that the SEMS coast are often affected by external anthropogenic inputs containing N and P (Kress & Galil, 2016), we hypothesized that nutrients limitation of phytoplankton and heterotrophic bacteria may be shifted to B 12 . Moreover, similarly to dissolved inorganic nutrients (e.g., orthophosphate, nitrate) and chlorophyll‐ a , surface B 12 concentrations in the Mediterranean Sea decreases as going eastward towards more oligotrophic waters (Bonnet et al., 2013).…”
Section: Introductionmentioning
confidence: 99%